Insight on recently discovered PET polyester‑degrading enzymes, thermostability and activity analyses - Leow, Adam Thean Chor; Mohd Yahaya, Normi; Mohd Shariff, Fairolniza; Bataiya, Sunusi Buhari; Nezhad, Nima Ghahremani (SpringerOpen, 2024)
The flexibility and the low production costs offered by plastics have made them crucial to society. Unfortunately, due to their resistance to biological degradation, plastics remain in the environment for an extended period of time, posing a growing risk to life on earth. Synthetic treatments of plastic waste damage the environment and may cause damage to human health. Bacterial and fungal isolates have been reported to degrade plastic polymers in a logistic safe approach with the help of their microbial cell enzymes. Recently, the bacterial strain Ideonella sakaiensis (201-F6) was discovered to break down and assimilate polyethylene terephthalate (PET) plastic via metabolic processes at 30 °C to 37 °C. PETase and MHETase enzymes help the bacterium to accomplish such tremendous action at lower temperatures than previously discovered enzymes. In addition to functioning at low temperatures, the noble bacterium's enzymes have amazing qualities over pH and PET plastic degradation, including a shorter period of degradation. It has been proven that using the enzyme PETase, this bacterium hydrolyzes the ester linkages of PET plastic, resulting in production of terephthalic acid (TPA), nontoxic compound and mono-2-hydroxyethyl (MHET), along with further depolymerization of MHET to release ethylene glycogen (EG) and terephthalic acid (TPA) by the second enzyme MHETase. Enzymatic plastic degradation has been proposed as an environmentally friendly and long-term solution to plastic waste in the environment. As a result, this review focuses on the enzymes involved in hydrolyzing PET plastic polymers, as well as some of the other microorganisms involved in plastic degradation.